Visible Watermarking Based on Multi-parameters Adjustable Gamma Correction - Lin, Chu-Hsing; Lee, Chen-Yu; Yang, Tzu-Chien; Lai, Shin-Pin (My University, 2011)
With the progress of information technology, digital data is a major trend of business communication today. Therefore, copyright protection of digital data has been an important research issue of information security. In the paper, we proposed an improved visible watermark scheme using multi-parameters adjustable Gamma Correction to reduce the distortion, which can increase color saturation. Our experiments showed that the PSNRs of the stego images with watermark embedded were up to 54.50 dB and 58.66 dB.
Keywords: visible watermark; copyright protection; Gamma Correction; PSNR